Online learning: a post COVID-19 alternative pedagogy for university students / Sandra Phek-Lin Sim, Hannah Phek-Khiok Sim and Cheng-Sim Quah - Sim, Sandra Phek-Lin; Sim, Hannah Phek-Khiok; Quah, Cheng-Sim (Universiti Teknologi MARA, 2020)
The sudden COVID-19 pandemic situation experienced globally has caused many schools and institutions of higher learning to resort to fully online teaching and learning throughout the world, including Malaysia. As many educators and students braved the situation, and until a remedy is found to prevent the spread of this deadly coronavirus, the question that lingers in the mind of many people is ‘Will online learning be the way forward for university students in post COVID-19’? Most past research have reported on students’ experience of online mode of learning via a blended learning approach but there is relatively little research focusing on the real experience of students embarking on full online learning mode, especially in the state of Sarawak. Thus, this quantitative research aimed to identify the level of acceptance of online learning among university students who have experienced full online learning mode. It also intended to identify the factors that facilitated online learning and the challenges of online learning among university students. Data were collected using an online survey involving 156 respondents from a public university in the state of Sarawak. The data collected from the survey were analysed using descriptive statistics (means, frequency counts and percentages). Results showed a moderate high level of acceptance of online learning among the university students. In addition, results revealed that among the four main factors that facilitated online learning among the students, enhancement of English language skills ranked the highest, followed by enthusiasm, self-efficacy and satisfaction. This study also found that among the main challenges encountered by the majority of the students are issues of delivery speed of teaching and learning, students’ attitude, struggles and stress of online learning mode. Results yielded in this study add to the existing literature on the possibility of online learning as an alternative pedagogy in post COVID-19 for the education sector.